Pengaruh Modal Kerja Terhadap Profitabilitas Pada Perusahaan Sektor Properti, Real Estate, Dan Konstruksi Bangunan Yang Terdaftar di BEI Periode 2014-2018 - Alvin Horianto; Putu Anom Mahadwartha; Arif Herlambang (Perpustakaan Universitas Surabaya, 2020)
Abstract— Working capital is very important for every company. Working capital needed to finance corporate activity and affect the company's ability to generate operating profits. The purpose of this study was to determine the influence the effectiveness of working capital which is measured by number of days accounts receivable (NDAV), number of days inventories (NDIV), number of days accounts payable (NDAP) of operating income, as measured by Gross Operating Income (GOI) in the Property, Real Estate, and Building Construction companies listed on Bursa Efek Indonesia in 2014-2018. This research is expected to give contributions to the management company associated with working capital and also as a reference for future research. This study was shaped by causal associative data analysis techniques using statistical analysis software with the help of Eviews 2010. Analysis techniques were used to determine how independent variables influence number of days accounts receivable (NDAV), number of days inventories (NDIV), number of days accounts payable (NDAP) of the dependent variable is Gross Operating Income (GOI), both simultaneously and partial. Keywords: Number of Days Accounts Receivable, Number of days Inventories, Number of Days Accounts Receivable, Gross Operating Income Abstrak— Modal kerja merupakan hal yang sangat penting bagi setiap perusahaan. Modal kerja sangat dibutuhkan untuk membiayai aktivitas perusahaan dan mempengaruhi kemampuan perusahaan dalam menghasilkan laba usaha. Tujuan penelitian ini adalah untuk mengetahui pengaruh efektifitas modal kerja yang di ukur dengan number of days accounts receivable (NDAV), number of days inventories (NDIV), number of days accounts payable (NDAP) terhadap laba usaha yang diukur dengan Gross Operating Income (GOI) pada perusahaan kontruksi bangunan / Gedung yang terdaftar di Bursa Efek Indonesia pada period 2014-2018. Penelitian ini diharapkan dapat memberikan sumbangan pemikiran bagi pihak manajemen perusahaan berkaitan dengan modal kerja dan juga sebagai referensi bagi penelitian selanjutnya. Jenis penelitian ini berbentuk asosiatif kausal dengan teknik analisis data menggunakan analisis statistik dengan bantuan software Eviews 2010. Teknik analisis tersebut digunakan untuk mengetahui bagaimana pengaruh variabel-variabel independen yaitu number of days accounts receivable (NDAV), number of days inventories (NDIV), number of days accounts payable (NDAP) terhadap variabel dependen yaitu Gross Operating Income (GOI) baik secara simultan maupun parsial. Kata kunci: Periode Penagihan Piutang, Periode Penyimpanan Persediaan, Periode Penagihan Hutang, Laba Kotor Operasional